2021
DOI: 10.1021/acs.inorgchem.1c02657
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photochromic Coordination Polymer by Phototriggered Subtle Molecular Conformation Variations

Abstract: Photochromic materials are constructed with molecules accompanied by structural change after triggering by light, which are of great importance and necessity for various applications. However, because of space-confinement effects, molecule stacking of these photoresponsive chromophores within coordination polymers (CPs) always results in an efficiency decrement and a response delay, and this phenomenon will lead to a poor photochromic property. Herein, a CP (named CIT-E) with a 3-fold-interpenetrating network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…S4†). 34 Powder X-ray diffraction pattern (PXRD) of the ligand and CIT-Z powder were compared with the simulated pattern generated by Mercury 4.1.0 software, and it was found that the main diffraction peaks in the CIT-Z test pattern match well with the simulated pattern (Fig. 2).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…S4†). 34 Powder X-ray diffraction pattern (PXRD) of the ligand and CIT-Z powder were compared with the simulated pattern generated by Mercury 4.1.0 software, and it was found that the main diffraction peaks in the CIT-Z test pattern match well with the simulated pattern (Fig. 2).…”
Section: Resultsmentioning
confidence: 86%
“…Herein, a CPs (named CIT-Z) was prepared using TPE pyridine derivative as an organic ligand and copper iodide as a metal center according to our previous work. 34 The CPs exhibits a two-dimensional triple-interpenetrating network structure with excellent chemical stability and optical properties. Based on its structural characteristics and the interaction between it and target analytes, CIT-Z can be utilized for detecting various pollutants in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…CIT‐E exhibits a one‐dimensional chain structure and demonstrates reversible force‐induced fluorescence enhancement properties, highlighting the crucial role of coordination effects and topological structures in the optical properties of CPs. Notably, CIT‐E shows reversible force‐induced fluorescence enhancement only, in contrast to our previous work involving CIT‐Z, which suggests the influence of the E/Z configuration of the ligand on the structure, properties, and applications of different CPs [26]. Moreover, CIT‐E demonstrates excellent thermal and chemical stability, making it suitable for detecting explosive analogs such as 2,4‐dinitroaniline.…”
Section: Introductionmentioning
confidence: 66%
“…The ligand TPE‐2by‐2‐E was synthesized according to previous work [26–28], and the synthesis route is shown in Supporting Information Figure S1. See the details in Figures S2–S4.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Due to the structural diversity, luminescence properties and various coordination modes of CuI clusters, a large number of copper iodide complexes with various structures can be obtained after coordinating with organic ligands. 5 These diverse CPs can exhibit a wide range of properties, such as stimulus-response, 6 conductivity, 7 catalysis 8 and magnetic properties. 9 In addition, owing to the abundant reserves in nature and low price and toxicity of the metal copper, CuI CPs are very attractive from the economic and environmental perspectives.…”
Section: Introductionmentioning
confidence: 99%